Implementation of the Integrated Employee Performance Information System (SIJAPATI) to Support the Transformation of Personnel Management - Nadya Salsabilla Stephanie; Siti Khumayah (Journal Of Social Science (JoSS), 2026)
The application of information technology in managing Civil Servant (Aparatur Sipil Negara or ASN) performance represents a strategic step toward more effective, transparent, and accountable personnel governance. The Kuningan Regency Government, through the Civil Service and Human Resource Development Agency (Badan Kepegawaian dan Pengembangan Sumber Daya Manusia or BKPSDM), developed the Integrated Employee Performance Information System (Sistem Informasi Kinerja Terpadu or SIJAPATI) as a digital platform for ASN performance management and reporting. This study aims to examine the implementation of SIJAPATI in supporting the transformation of personnel governance at BKPSDM Kuningan Regency. Using a qualitative method with a descriptive approach, data were collected through observations, interviews, and documentation involving the Head of BKPSDM, the Division of Performance Evaluation, Welfare, and Civil Service Development, SIJAPATI operators, and ASN users. The analysis applied George C. Edward III’s policy implementation theory, which consists of four dimensions: communication, resources, disposition, and bureaucratic structure. The results indicate that SIJAPATI implementation is supported by continuous socialization, coordination among implementers, and the utilization of information technology. Supporting factors include clear regulatory frameworks, human resource and technological support, positive user attitudes, and structured operational mechanisms. However, several challenges were identified, including user adaptation processes, technical issues during the initial implementation phase, and varying levels of ASN digital literacy. To address these challenges, BKPSDM provides guidance, consultation services, periodic evaluations, and system improvements tailored to user needs and regulatory developments. Therefore, SIJAPATI contributes transformation of personnel governance by promoting a more integrated, transparent, and performance-oriented management system for ASN